The Relationship Between Students’ Learning Motivation and Their English Achievement - Akhmad Ghifari; Adelia Salsabila; Reihan Norfansyah; M. Rayhandi Pratama; Muhammad Syahriwan; Abdul Syahid (Didascein : Journal of English Education, 2026)
Learning motivation is considered one of the factors that may influence students’ academic achievement, especially in learning English as a foreign language. This study aimed to investigate the relationship between students’ learning motivation and their English achievement among fourth-semester students of the English Education Department. The study employed a quantitative correlational research design. Data were collected using a learning motivation questionnaire distributed through Google Form and students’ English achievement scores obtained from academic records. The questionnaire consisted of positive and negative statements related to students’ motivation in learning English and employed a five-point Likert scale ranging from Strongly Agree to Strongly Disagree. The participants of this study were 20 fourth-semester students of the English Education Department. The data were analyzed using descriptive statistics, the Shapiro–Wilk normality test, and Spearman rank correlation. The findings showed that most students demonstrated high levels of learning motivation and satisfactory English achievement. The correlation analysis revealed a low positive relationship between students’ learning motivation and English achievement (ρ = 0.229). However, the significance value (p = 0.330) indicated that the relationship was not statistically significant. These findings suggest that learning motivation alone may not significantly determine students’ English achievement, as academic performance may also be influenced by other factors such as learning strategies, teaching methods, self-confidence, and classroom environment. The findings of this study are expected to contribute to English teaching practice by encouraging lecturers to maintain students’ motivation through meaningful learning activities, constructive feedback, collaborative learning, and supportive classroom environments.